Recuperación de nutrientes provenientes de la micción humana para el saneamiento sostenible en el casco urbano de la ciudad de Latacunga 2019-2020. - Sisa Paca, Miguel Ángel (2020)
This research work refers to the recovery of nutrients from human male urination in the urban area of the Latacunga city , each human being generates 1.5 liters of urine per day, which makes it more difficult to manage this type of waste, conventional treatments not only consume and pollute resources, but also are executed in a careless and ephemeral way. In Latacunga city, there is evidence of urban sites affected by the deposition of human urination, the places considered as patrimonial are affected generating a bad image for the city, this problem does not only reside in the people with bad habits, if not in the lack of places for its disposition, for what to implement measures that help to mitigate this affliction is an obligation for the conservation of the different cultural areas of the urban area Ten places were identified as potentially being most affected by heritage sites in the city, with priority given to public spaces and areas of historical importance. The model for urine collection was designed considering the anthropometry of people, the number of individuals who can use it and considering strategies to reduce the visual pollution generated by the device. The urine collector has a collection capacity of 70 L. An alternative was proposed for the recovery of nutrients from human micturition from the implementation of ecological toilets, in which urine can be collected to be used later in the production of organic fertilizer and thus reduce the impact of pollution in public spaces and heritage of Latacunga city.